Impact Of Level and Quality of Family Support to Women During Second Trimester and The Maternal and Fetal Outcome - Mane, Ujwala R.; Salunkhe, Jyoti A.; Mohite, Vaishali R.; Jadhav, Vikas; Phuke, Manda (Journal of Neonatal Surgery, 2025)
Background: Pregnancy constitutes a time of significant life change requiring psychological adjustment to maintain health which is important for unborn child. Family support may be one of the determinants of life style habit and relevant health behavior for pregnancy outcome. In India, joint family system is practiced, now a day’s due to education, urbanization and industrialization in the Indian society, the family institution continues to play a central role in the lives of people1. Due to busy schedule and changing in working pattern most of women remain out of home for longer period. But in rural areas women are depend on mother in law and husband for decision2. During pregnancy, women undergo various biological, chemical, physiological, and emotional changes which modify their quality of life and well-being, the Impact of perceived Social Support from Family and Empowerment on Maternal Wellbeing in the Postpartum Period3. So by doing the present research study it will be bridging the gap between family and pregnant women, this study will suggest communications needed to gain better maternal and fetal outcome. Due to family support early diagnosis and prevention of any complications can be ruled out. Aim and Objectives: It was aimed to assess the impact of level and quality of family support during second trimester, to find an association between impact of level and quality of family support and maternal and fetal outcome and to find an association between sociodemographic variables and impact of level and quality of family support during second trimester. Material and Methods: A survey research design with quantitative approach was adopted for this study. The study was conducted at four Primary Health Centres at Karad, Maharashtra, India i.e. Rethare, Vadgaon, Kale and Supane. Simple random sampling with consecutive sampling was used for selecting the 344 subjects from Rethare, Vadgaon, Kale and Supane areas of Karad Taluka. Data collected before completion of first three months of pregnancy, then during second trimester and after delivery. Data was analyzed by using descriptive and inferential statistics. Result: findings of study shows that significant association found between maternal outcome with presence of close relatives before delivery, family support received after delivery, (p<0.05). Results: related to fetal outcome and family support shows that there was no significant association found between fetal outcome with level of psychosocial support during second trimester (p>0.05).